2018
DOI: 10.1101/291062
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparison of Genotypic and Phenotypic Correlations: Cheverud’s Conjecture in Humans

Abstract: Accurate estimation of genetic correlation requires large sample sizes and access to genetically informative data, which are not always available. Accordingly, phenotypic correlations are often assumed to reflect genotypic correlations in evolutionary biology. Cheverud's conjecture asserts that the use of phenotypic correlations as proxies for genetic correlations is appropriate. Empirical evidence of the conjecture has been found across plant and animal species, with results suggesting that there is indeed a … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 34 publications
(31 reference statements)
0
11
0
Order By: Relevance
“…Given that under the “Cheverud’s Conjecture” 20,21 genetic correlations can be used as proxies of phenotypic correlations, we can use the genetic correlations obtained from LDscore regression for the GWAS of Y*, X* and λ to fit (3) using GenomicSEM 22 .…”
Section: Proposed Correction Methods and Implementation In Genomicsemmentioning
confidence: 99%
“…Given that under the “Cheverud’s Conjecture” 20,21 genetic correlations can be used as proxies of phenotypic correlations, we can use the genetic correlations obtained from LDscore regression for the GWAS of Y*, X* and λ to fit (3) using GenomicSEM 22 .…”
Section: Proposed Correction Methods and Implementation In Genomicsemmentioning
confidence: 99%
“…Therefore, the recent H. sapiens pooled within-population P matrices for the occipital and frontal bones were used as proxies for H. erectus. H. sapiens was chosen because it is the closest extant phylogenetic match for H. erectus [49,52,80] and the human P matrix is a good estimate of its G matrix [81][82][83]. In total, 145 recent H. sapiens from three populations with n ∼ 50 each were used to calculate the pooled within-population covariance matrices that were used as proxies for H. erectus in testing Prediction 3 (electronic supplementary material, table S3).…”
Section: (C) Predictionmentioning
confidence: 99%
“…The concept of morphological integration encompasses the pattern and the amount of correlation between different morphological traits (the socalled variables), which is detected by the analysis of correlation coe cient matrices 23 . Recently, Sodini et al supported the correlation between the morphological traits and the genetic and phenotypic features 24 . We have found that the correlation among the landmarks set within a single linear module (i.e.…”
Section: Discussionmentioning
confidence: 97%